Molecular and Structural Analysis of the Helicobacter pylori cag Type IV Secretion System Core Complex - Frick-Cheng, Arwen E. (mBio, 2016)
Bacterial type IV secretion systems (T4SSs) can function to export or import DNA, and can deliver effector proteins into a wide range of target cells. Relatively little is known about the structural organization of T4SSs that secrete effector proteins. In this report, we describe the isolation and analysis of a membrane-spanning core complex from the Helicobacter pylori cag T4SS, which has an important role in the pathogenesis of gastric cancer. We show that this complex contains five H. pylori proteins, CagM, CagT, Cag3, CagX, and CagY, each of which is required for cag T4SS activity. CagX and CagY are orthologous to the VirB9 and VirB10 components of T4SSs in other bacterial species, and the other three Cag proteins are unique to H. pylori. Negative stain single-particle electron microscopy revealed complexes 41 nm in diameter, characterized by a 19-nm-diameter central ring linked to an outer ring by spoke-like linkers. Incomplete complexes formed by Δcag3 or ΔcagT mutants retain the 19-nm-diameter ring but lack an organized outer ring. Immunogold labeling studies confirm that Cag3 is a peripheral component of the complex. The cag T4SS core complex has an overall diameter and structural organization that differ considerably from the corresponding features of conjugative T4SSs. These results highlight specialized features of the H. pylori cag T4SS that are optimized for function in the human gastric mucosal environment.